Enhancing Students' Communication Skills in Social Studies Learning Through Cooperative Learning - Mumun Munawaroh; Etty Ratnawati; Tri Zahra Ningsih; Nuryana Nuryana (Ta'dib, 2022)
The goal of this study is to explore how cooperative learning methods affect students' communication skills in social studies classes. This study employed a randomized pretest-posttest control group design as an experimental design. The sample is made up of 60 students who were chosen using the proportional sampling technique from the 184 students in class VII that make up the population. The communication skills assessment sheet is a tool for gathering information. Analysis The research findings were examined using a quantitative descriptive technique. The data were analyzed and the effect of treatment on the variables was determined using the t-test statistical test. The findings indicate that using a cooperative learning model in social studies learning can help improve students' communication skills. The results of this study promote the development of 21st century education, particularly in terms of supporting students to possess the 4C skills, of which communication skills are one.